Pemanfaaatan Opencart Sebagai Media Promosi Dan Pengembangan Usaha Mikro, Kecil Dan Menengah Di Bukittinggi - Al Hafidz Al Parisi, Muhammad Husein; Almukarrom Ramadhan, Sayyid Barqi (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) now have more chances to increase their competitiveness in a market that is becoming more and more competitive due to the quick growth of digital technology. Nonetheless, a large number of MSMEs in Bukittinggi continue to market their goods via traditional methods including word-of-mouth, direct sales, and local exhibits. Slow business growth is the outcome of these advertising strategies' constraints in reaching a larger market. Using Opencart as a web-based promotional tool, this study seeks to address these issues. MSMEs should be able to access a wider audience, make their products more visible, and run their businesses more effectively via this platform. Four stages make up the development model used in this study, which employs the Research and Development (R&D) method: define (user needs), design (system design), create (application development), and disseminate (results). The outcome of this study is a web-based marketing tool created with Opencart. MSMEs may easily manage products, digitally display catalogs, and complete online transactions with this solution. The results of the study demonstrate that Opencart can boost marketing reach, improve promotional efficacy, and support the expansion of MSMEs in Bukittinggi. As a result, Opencart may be a useful tool for helping MSMEs in the modern day with their digital transformation. Additionally, with its appealing design and user-friendly navigation, this web-based promotional material can give customers a better shopping experience. In the long run, it is anticipated that MSMEs will benefit from this enhanced digital presence by seeing an increase in revenue and client loyalty. Opencart can therefore be a useful tool for assisting MSMEs in their digital transition and enhancing their ability to compete in the industrial age.